2009
DOI: 10.1080/10669860903133310
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Retail Internationalization on Agribusiness: The Case of Ukraine

Abstract: This article aims to reveal the impact of the retail internationalization process on the Ukrainian agribusiness. Building on an in-depth survey, we delineate major changes that occur owing to the process. Talking about global retailers, an essential part of their business is connected with selling high-quality products. Because (food) quality and thereby food safety processes are considered to be the highest priority, we concentrate on the agri-food business. Our interest in Ukraine is kindled by ongoing verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…A similar example has been shown for the Ukraine agri-food business. Suppliers of well-known foreign processors and retailers had fewer problems obtaining loans at more favorable interest rates because to some extent, doing business with a foreigner was regarded as a kind of status symbol (Gagalyuk and Hanf 2009). Taking into account the discussed issues, the use of referent power is highly advisable.…”
Section: Resultsmentioning
confidence: 99%
“…A similar example has been shown for the Ukraine agri-food business. Suppliers of well-known foreign processors and retailers had fewer problems obtaining loans at more favorable interest rates because to some extent, doing business with a foreigner was regarded as a kind of status symbol (Gagalyuk and Hanf 2009). Taking into account the discussed issues, the use of referent power is highly advisable.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, modern IT-infrastructure is seldom used. Such circumstances substantially impede procurement relationships between actors (Gagalyuk and Hanf, 2009).…”
Section: Methodology Survey Designmentioning
confidence: 99%
“…These processes are business inter nationalisation and verticalisation. With regard to business internationalisation, an important remark is that financially strong Western companies have the capability of disrupting the structure of foreign markets and installing their own business ideas in new market environments on a grand scale Gagalyuk and Hanf, 2009;Swinnen, 2006). It has been observed that the internationalising firms try to arrange a sound supply side for their business abroad.…”
Section: Methodology Survey Designmentioning
confidence: 99%
“…Beberapa dapatan empirikal tentang strategi pengantarabangsaan juga telah dikenalpasti seperti strategi kolaborasi (Theuvsen & Ebneth 2005), strategi rantaian dan mod penembusan ke pasaran asing (Benito & Strøm 2000), kaedah pengekspotan (Jank, Leme & Nassar 2000) serta penentuan keputusan untuk ekspot (Ayouz & Remaud 2003). Selain itu, kajian lepas juga mendapati impak pengantarabangsaan dalam industri agro telah dikupas seperti kesan terhadap proses pengantarabangsaan (Gagalyuk & Hanf 2009), jarak budaya (Filippaios & Rama 2011), evolusi pasaran makanan dan kesan pengantarabangsaan runcit (Hanf & Belaya 2008).…”
unclassified
“…Dari segi konteks kajian pula, pengantarabangsaan industri perniagaan agro banyak melibatkan negara yang sudah membangun dan tergolong dalam perindustrian maju seperti Amerika Syarikat (Hughes, Kennedy & Ortego 1999), Jerman (Theuvsen & Ebneth 2005;Theuvsen & Heyder 2011), Australia (Jordan, Shuji & Izawa 2006) dan New Zealand (Ibeh 2005). Manakala di negara pasaran baru muncul pula, kajian telah dilakukan di Thailand (Goss & Burch 2001), Indonesia (Suprehatin 2013), Ukraine (Gagalyuk & Hanf 2009), Brazil (Jank et al 2000), India (Raju 2014), Turkey (Fidan 2016), Malaysia (Senik, Mat Isa, MdSham & Ayob 2014) dan China (Xiaoyun 2012). Walaupun terdapat peningkatan jumlah penyelidikan mengenai syarikat perniagaan agro yang beroperasi di peringkat antarabangsa bagi negara pasaran baru muncul, namun sehingga kini, kajian yang menjurus kepada strategi pengantarabangsaan yang memfokus kepada strategi mod kemasukan asing dan pilihan pasaran yang mempengaruhi corak pengantarabangsaan di kalangan negara pasaran baru muncul masih kurang.…”
unclassified